Labor Pain Assessment and Management by Using RAT Model Framework - Tanglakmankhong, Kamonthip; Ngamkham, Srisuda; Chotiga, Pleumjit; Thaewpia, Supawadee (Journal of Phrapokklao Nursing College, Chanthaburi, 2018)
-